The SAGES Atlas of Robotic Surgery (Springer International Publishing, 2018)
This book is intended as a definitive, state of the art guide to robotic surgery that summarizes the field for surgeons at all levels. More specifically, its goals are threefold: to review the basics of robotic surgery, including fundamental principles, technology, operating room setup, and workflow; to describe and illustrate the procedures most commonly performed in a robotic operating room; and to discuss key issues relating to cost, adoption, and training. Procedures from many surgical disciplines are included, which aid robotic surgeons in supervising and assisting colleagues in these disciplines and simultaneously heighten their awareness of the tricks and tools used in other disciplines that can be retasked for their own purposes. In addition, the future prospects for robotic surgery, including anticipated developments in equipment, are discussed. The SAGES Atlas of Robotic Surgery is an excellent aid for residents and fellows entering the field, as well as a welcome update on recent progress for practicing robotic surgeons and an ideal primer for senior surgeons adapting these new technologies to their current practice.